2003
DOI: 10.5483/bmbrep.2003.36.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Circulating Melanoma Cells by a Two-marker Polymerase Chain Reaction Assay in Relation to Therapy

Abstract: Malignant melanoma is one of the most rapidly increasing cancer types, and patients with metastatic disease have a very poor prognosis. Detection of metastatic melanoma cells in circulation may aid the clinician in assessing tumor progression, metastatic potential, and response to therapy. Tyrosinase is a key enzyme in melanine biosynthesis. The gene is actively expressed in melanocytes and melanoma cells. Melan A is a differentiation antigen that is expressed in melanocytes. The presence of these molecules in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…[7] A two-marker polymerase chain reaction (PCR) using melan-A and tyrosinase has been described for the detection of Circulating Malignant Cells (CMCs) in the peripheral blood of patients with skin melanoma. [8] The combination of these two markers was also described for the detection of CMCs in uveal melanoma. [9,10] However, only a few studies evaluated the co-expression of these immunohistochemical markers in primary uveal melanomas.…”
Section: Introductionmentioning
confidence: 99%
“…[7] A two-marker polymerase chain reaction (PCR) using melan-A and tyrosinase has been described for the detection of Circulating Malignant Cells (CMCs) in the peripheral blood of patients with skin melanoma. [8] The combination of these two markers was also described for the detection of CMCs in uveal melanoma. [9,10] However, only a few studies evaluated the co-expression of these immunohistochemical markers in primary uveal melanomas.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it is accepted that presence of CMCs is correlated with the clinical stage of patients and that detection of these cells in patients with early-stage disease may indicate a high risk of metastasis and a lower probability of overall survival [13]. Recent studies described tyrosinase RT-PCR results as a potentially useful molecular marker that may provide an early indication of therapy effectiveness [14]. However, other authors found no relationship between positive PCR for tyrosinase and disease-free or overall survival [15].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, MITF should also be analyzed in sequential multiple blood samples in further studies. It has also been shown that the detection of circulating melanoma cells in serial blood samples obtained before, during, and after treatment (immunotherapy, chemotherapy, or biochemotherapy) can be used to monitor patients' response to treatment [9,12,14,27,28,32]. Koyanagi et al [38] have shown that MITF detection decreased with adjuvant biochemotherapy treatment and that MITF detection after the treatment was associated with significantly lower survival.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, several studies have shown that multiple-marker analysis allows for the detection of circulating melanoma cells in a higher percentage of melanoma patients than single-marker analysis [9][10][11][24][25][26][27][28]30,36]. Among the markers analyzed in these studies, some have shown high specificity for melanoma cells (MART-1, TRP-1, TRP-2, MAGE-3, paired box homeotic gene transcription factor 3, b1-4-N-acetylgalactosaminyltransferase), whereas others were found to be positive also in healthy volunteer samples (p97, MUC18, gp100) [9][10][11][24][25][26][27]30,36]. Our study has confirmed the advantage of multi-marker analysis for the detection of circulating melanoma cells that had been shown in earlier studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation